Crystal structure of 7,9-dimethoxy-2-methyl-4-propylbenzo[f]isoquinolin-5-yl 4-bromobenzoate, C26H24BrNO4 - Wang Jia-Jia; Feng Hao-Yun; Wang He-Ting; Sun Qing-Gang; Li Qian-Li; Zhang Ya-Lin (Zeitschrift für Kristallographie - New Crystal Structures)
C26H24BrNO4, monoclinic, P21/c (no. 14), a = 11.0275(5) Å, b = 21.172(10) Å, c = 10.145(4) Å, β = 103.929(8)°, V = 2298.9(17) Å3, Z = 4, R gt(F) = 0.0653, wR ref(F 2) = 0.2027, T = 296 K.